2013
DOI: 10.3389/fnene.2013.00002
|View full text |Cite
|
Sign up to set email alerts
|

Glucagon-like peptide-1 (GLP-1) raises blood-brain glucose transfer capacity and hexokinase activity in human brain

Abstract: In hyperglycemia, glucagon-like peptide-1 (GLP-1) lowers brain glucose concentration together with increased net blood-brain clearance and brain metabolism, but it is not known whether this effect depends on the prevailing plasma glucose (PG) concentration. In hypoglycemia, glucose depletion potentially impairs brain function. Here, we test the hypothesis that GLP-1 exacerbates the effect of hypoglycemia. To test the hypothesis, we determined glucose transport and consumption rates in seven healthy men in a ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
30
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
2

Relationship

4
5

Authors

Journals

citations
Cited by 25 publications
(36 citation statements)
references
References 45 publications
5
30
0
1
Order By: Relevance
“…The binding in the AD patients was the more significant measure, but the group as a whole had marked decrease of the sCBF estimates, particularly in FL and PL, as previously reported by Johannsen et al (2000). This finding is of considerable interest because a matching decline of glucose metabolism generally is not present (Edison et al, 2007), although lowered metabolism generally is evident also in FL in addition to the pathognomonic decline in parietal lobe (Gejl et al, 2012, 2013, 2014, 2016). The low flow may be a physiological reaction to the functional decline of the diseased brain, as oxygen delivery is commensurate with the reduced consumption of oxygen (Rodell et al, 2012).…”
Section: Discussionsupporting
confidence: 61%
“…The binding in the AD patients was the more significant measure, but the group as a whole had marked decrease of the sCBF estimates, particularly in FL and PL, as previously reported by Johannsen et al (2000). This finding is of considerable interest because a matching decline of glucose metabolism generally is not present (Edison et al, 2007), although lowered metabolism generally is evident also in FL in addition to the pathognomonic decline in parietal lobe (Gejl et al, 2012, 2013, 2014, 2016). The low flow may be a physiological reaction to the functional decline of the diseased brain, as oxygen delivery is commensurate with the reduced consumption of oxygen (Rodell et al, 2012).…”
Section: Discussionsupporting
confidence: 61%
“…The hypoglycaemia condition revealed that effects of native GLP‐1 on glucose metabolism in brain depend on the plasma glucose concentration , as in other tissues, notably beta cells in pancreas . Thus, GLP‐1 does not alter brain glucose metabolism or transport during hypoglycaemia.…”
Section: Glp‐1 and Cerebral Glucose Metabolismmentioning
confidence: 98%
“…Thus, GLP‐1 does not alter brain glucose metabolism or transport during hypoglycaemia. However, the GLP‐1 treatment led to a lower estimate of vascular volume in the brain . We did not determine cerebral blood flow in that study, but the glucose unidirectional and net clearances are measures that in principle incorporate effects of blood flow, expressed by the changes of extraction fractions (unidirectional and net).…”
Section: Glp‐1 and Cerebral Glucose Metabolismmentioning
confidence: 99%
“…For example, under conditions of hyperglycemia, peripherally administered GLP-1 increases the phosphorylation velocity ( V max ) of neuronal hexokinase while also increasing blood–brain glucose transport capacity ( T max ). 157,158 …”
Section: Glucoregulatory Properties Of Glp-1 Mediated By the Nervomentioning
confidence: 99%